2007
DOI: 10.1007/s11255-007-9221-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of PSA flare-up in patients with hormone-refractory prostate cancer undergoing chemotherapy

Abstract: A considerable portion of HRPC patients experience an initial PSA flare-up under systemic chemotherapy. In this study, occurrence of flare-up phenomenon did not impact survival. Chemotherapy should be continued a minimum of six weeks before removing patients from a docetaxel-based regimen. We showed evidence that co-medication with dexamethasone/prednisolone and/or estramustine itself can induce an initial PSA flare-up via androgen receptor mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
22
2
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 32 publications
(35 reference statements)
6
22
2
2
Order By: Relevance
“…Olbert et al showed better survival in men with PSA flare or PSA decline than men with PSA failure. Similarly, Sella et al and Nelius et al showed the same tendency although statistical significance was not reached, consistent with the OS data in the present study. Thus, the prognosis in men with PSA flare seems to be equivalent to that of PSA responders, and superior to that of men with PSA failure.…”
Section: Discussionsupporting
confidence: 90%
“…Olbert et al showed better survival in men with PSA flare or PSA decline than men with PSA failure. Similarly, Sella et al and Nelius et al showed the same tendency although statistical significance was not reached, consistent with the OS data in the present study. Thus, the prognosis in men with PSA flare seems to be equivalent to that of PSA responders, and superior to that of men with PSA failure.…”
Section: Discussionsupporting
confidence: 90%
“…The PSA response and the relief of bone pain may aid the recognition of these pitfalls in the clinical images, and in consequence, support the continuation of the chemotherapy treatment. Similarly, cases of PSA flare phenomenon (28) and pain flare phenomenon (29) have been previously reported. Therefore, it has been proposed that the pain and PSA response are associated with survival, but are not adequate to use as surrogate end points, according to the TAX-327 study, which developed a prognostic model and nomogram using baseline clinical variables to predict mortality among males diagnosed with castration resistant prostate cancer (8,9).…”
Section: Discussionsupporting
confidence: 58%
“…However, it is important to be aware of the PSA flare-up phenomenon, which leads to a transient PSA elevation following chemotherapy (13). In the current study, two patients exhibited an increase in their PSA levels on initiation of treatment, which was followed by a decline in PSA levels after five weeks (Table IV).…”
Section: Discussionmentioning
confidence: 99%